(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
XML Parallel parsing based upon multicore is a very efficient technique. It will also increase the performance of the system while xml parsing .The idea is to increase the number of threads based upon the CPU cores. By doing this the throughput & the performance of the CPU is increased as making the use of multiple threads on every CPU core. Hence it improves the overall CPU Utilaization & Speed-Up the Data read/write operations.